Modified Le Fort II approach with adequate vascularization preservation in midface allotransplantation: Mock surgery - Chao-Hsin Huang; Yur-Ren Kuo; Yi-Chia Wu; Hsiao-Chen Lee; Su-Shin Lee (Asian Journal of Surgery, 2022)
Introduction: It is critical to preserve adequate vascularization in midface allotransplantation, the major complication of which is inadequate blood supply in palate area supplying mainly by internal maxillary artery. Therefore, the aim of this study is to explore a modified Le Fort II approach entailing midface vascularization enhancement. Materials and methods: Ten cadaveric heads were used in mock surgery. A conventional approach was used on seven cadaveric heads to harvest external carotid artery-facial artery-internal maxillary artery axis. On the remaining three cadaveric heads, modified Le Fort II approach was applied where the internal maxillary artery was harvested after cutting off zygomatic arches and rami of the mandible. Results: The conventional approach had difficulty harvesting internal maxillary artery, which left the facial artery the only blood supply to midface. Modified Le Fort II approach with Computerized surgical planning (CSP) assisted, on the other hand, could completely unveil and harvest intact internal maxillary artery after osteotomy of mandibular ramus. Conclusion: The modified Le Fort II approach with CSP and ultrasonic bone cutter assisted can maximally preserve internal maxillary system with ease. This approach optimizes midface allotransplantation in clinical practice in future.